Constantin Petrescu-Ercea: A Route of Translations from Scandinavian Literature: The Role of a Transylvanian Intellectual in the Transmission of Nordic Literature in Romania in the First Decades of the 20th Century - Hodârnău, Ioana (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2021)
The present study aims at analysing the ways in which the Nordic literature and culture circulates in a European context in the first half of the 20th century. In this way, French language functions as lingua franca for translations from most of the foreign literatures, being the main “guarantor” of the reception of marginal cultures and literatures. It is also the case for the Romanian cultural space, whereas Scandinavian literature attain visibility in Romania through French intermediate. Moreover, this acquisition of Nordic literature in the Romanian space in the 1920’s is accomplished in a unique way, through a private library. Our research paper tackles the reception of literary texts from Danish, Norwegian and Swedish literature in Romania, a cultural path made possible due to the existence of a private library own by an interwar Romanian intellectual, Constantin Petrescu-Ercea. With PhD studies in law at Sorbonne University, Petrescu-Ercea represents one of the outstanding figures in the academic field in Transylvania, from the interwar period until the establishment of communism in Romania. Given these research directions, the present study aims to be a study in cultural history.